MITRAL VALVE STENOSIS - Zumrat Sh. Sadikova; Islambek A. Kudiyarov; Kadriddin Sh. Saifiddin Khoji; E’zoza E. Abdujabborova; Sa’dullokh A. Koriyev; Mokhinur S. Fayziyeva (Central Asian Journal of Medicine, 2025)
Mitral valve stenosis (Latin: stenosis ostii atrioventricularis sinistri stenosis, also known as mitral stenosis or narrowing of the left atrioventricular orifice) is a common heart disease. It leads to impaired diastolic blood flow from the left atrium to the left ventricle. The disease is characterized by a slow progression. The onset of symptoms is most often between the ages of 40 and 50. The disease is more common in women. There is a complaint of shortness of breath during physical exertion due to high pressure in the pulmonary arteries. This article will discuss the causes, symptoms and consequences of mitral valve stenosis, as well as methods of treatment and prevention.